HUBUNGAN GAYA KEPEMIMPINAN DENGAN MOTIVASI KERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT NUR HIDAYAH TAHUN 2021 - Sarlia Sarlia; Sumarni Sumarni Sumarni; Imram Radne Rimba Putri (Universitas Pahlawan Tuanku Tambusai, 2021)
The world health in Indonesia is currently growing very rapidly, it can be seen that number of hospital continues to grow. Every hospital needs human resources. HR itself is one of the most important assets in a company organization. Human resources who have work motivation, employees will work harder and create good performance. With that we need an encouragement that can help HR improve their performance. With the motivation to influence human resources to be more optimal in realizing the goals of the organization and the agency. High and low employee performance is influenced by several factors, one of which is leadership style. Thus study aims to determine the relationship between leadership style and work motivation of nurses in the Nur Hidayah Hospital Inpatient Room at in 2021. Research The approach used in this research is descriptive correlasional with cross sectional approach. The population in this study were nurses in the inpatient room at nur hidayah hospital with a total of 35 respondents. Then to analyze the data in this study using the sperm rank with the help of SPSS. Results: The results showed that there was a relationship between leadership style and work motivation of nurses in the inpatient room of nur hidayah hospital, where the correlation coefficient (r) was 0,343 with sig 0,044 (p